Does Care Transition Matter? Exploring the Newly Published HCAHPS Measure. (September 2020) - Hod, Rafael; Maimon, Oded; Zimlichman, Eyal
In recent years, health care systems have undergone a consumer revolution—putting patients at the center. The study aim was to explore the association between care transition —the new measure proposed by the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS)—and hospital patients' overall rating based on their experience, along with hospitals' internal characteristics and operational attributes. Using HCAHPS and American Hospital Association published databases, the authors examined the association between hospital characteristics and measures of patient experience, focusing on the care transition measure, in 2350 US hospitals. Positive significant association was found between care transition and overall rating ( P < .0001). An interaction regression model revealed that each of the following moderators—teaching affiliation, location, and membership in a health system—significantly (all P < .05) strengthens the association between care transition and overall rating in a positive direction. These findings may help improve hospital rating, value-based payments, and patient-centered outcomes.